Silagem de resíduo de uva como fonte de antioxidante em dietas com óleo de soja para vacas leiteiras - Santos, Nadine Woruby (2011)
The aim of this study was to evaluate the effect of feeding grape residue silage on the parameters: intake, nutrients digestibility, blood parameters and also production, chemical composition, fatty acid and oxidative stability of milk. It was used four Holstein cows, confined, average live weight of 504 +-} 26 kg and 136 +-} 28 days in milk, they were assigned in a Latin square with four treatments and four periods of 21 days each. The diets studied were: control diet with 4% soybean oil, diet with 4% soybean oil and 5% of grape residue silage, diet with 4% soybean oil and 7.5% of grape residue silage, diet with 4% soybean oil and 10% grape residue silage. It was determined the intake of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), non-fiber carbohydrates (NFC) . The estimated total apparent digestibility was performed for DM and nutrients, CP, EE, NDF, ADF and NFC. The blood was sampled from animals in starvation for analyzing glucose, triglycerides, total cholesterol, HDL, LDL and VLDL and N-urea. Milk production and milk yield corrected to 3.5% fat and density were measured as the milk components protein, fat, lactose, total solids, N-urea, somatic cell count (SCS) and composition of fatty acids. The oxidative stability of milk was determined by analysis of determination of total polyphenols, flavonoids, antioxidant activity and conjugated diene hydroperoxides (CD). It was observed that the grape residue silage did not alter the intake of DM, OM, NDF, ADF and NFC (P>0.05), however, the supply of this food diets resulted in higher EE intake (P=0.02). The total apparent digestibility of nutrients was affected by the levels of grape residue silage. DM digestibility was reduced linearly (P=0.02) as OM (P=0.03) and CP (P=0.03) with level of 7.5% DM of grape residue silage. The diets affected the digestibility of the NDF linearly negative (P=0.02) and ADF (P=0.01) and the results showed this effect with the 5% level in DM. The digestibility of EE and NFC were not influenced by treatments. Regarding blood parameters, concentrations of glucose, triglycerides, total cholesterol and HDL, LDL, VLDL and urea were not affected (P>0.05) by diets. Cows fed with the different levels of grape residue silage showed milk production equally as well as milk production adjusted to 3.5% fat (P>0.05). Milk components were not changed, however, there was a decreased (P=0.05) in levels of N-urea with diets containing 7.5% and 10% grape residue on dry matter. There was also no effect (P>0.05) of treatments on individual fatty acid composition and proportions. The concentrations of polyphenols in milk with the inclusion of grape residue silage were not significant, as the flavonoid content (P>0.05). The parameter of power reducing of milk was affected by diet (P=0.002) and the level of 10% grape residue silage showed higher power reducing, however, the higher antioxidant activity of milk did not result in lower production of CD (P>0.05). Grape residue silage can be used in feed for dairy cows because it keeps the production and milk quality and increases the antioxidant activity.